Perception of journalism students regarding TikTok as an informative tool - Miranda Galbe, Jorge (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
TikTok is a social network platform that has experienced exponential growth since 2020. Its operating mode, with short videos and based on the Skinner box, makes it one of the most addictive social media platforms. Its users, mainly teenagers and young adults, spend long periods of time consuming the content offered, thus becoming a powerful communication tool. This article analyzes the perception of journalism students regarding the social network TikTok as a tool for disseminating informative content. To do this, after conducting a practice on this social network in class, a survey was conducted among the students. This shows how, despite being very hesitant at first to use TikTok as an informative tool, they changed their assessment of it, perceiving it as a useful platform to develop their journalistic work.